Fastest, highest, youngest? Analysing the athlete`s experience of the Singapore Youth Olympic Games - Krieger, J. (International Review for the Sociology of Sport, 2013)
The Youth Olympic Games (YOG) are the newest addition to the Olympic Movement and, in light of recent discussions of the education of high-performance athletes, represent a change within the International Olympic Committee (IOC) from a philosophy of `winning by all means` to a philosophy much more informed by education. Therefore, this paper analyses the YOG through the experiences of participating athletes and puts their perception of the event in contrast to the policies of the IOC. Through the centring of the agents within the hermeneutic analysis, along with the use of Critical Discourse Analysis, a more relevant image of the YOG is constructed and it shows that that the perceptions of the athletes are in contrast to the policy documents. Whereas the organisation claims that the content of the Culture and Education Programme of the YOG was very successful and enhanced the educational experience of the athletes, the subjects of this study were in a way dissatisfied with the programme. Thus, their perceptions helped to deconstruct the political claims in a very valuable way and future, athlete-centred research is needed in order to enhance the educational and cultural effects of the YOG.